Analisis Metode Communicative Language Teaching terhadap Kemampuan Berbicara Bahasa Inggris Guru-Guru SMK dan SMP Islam Mandiri Bojong Gede Bogor - Iwan Budiarso (SAP (Susunan Artikel Pendidikan), 2019)
In learning English, speaking ability is a very important aspect, especially for teachers. Implementation in class, the teachers are expected to be good facilitators and motivators so their students have increasingly spirit in learning. One of teaching method that can be applied is Communicative Language Teaching (CLT). The purpose of this research is to build motivation, creativity, and teacher’s ability of speaking business English. Using this teaching method can give new learning experiences to the teachers. This research is a classroom action research in Yayasan Islam Terpadu Mandiri Bojonggede Bogor. There are two schools, SMK Mandiri and SMP Islam Mandiri. The total number of teachers are 35 people. They are the object of this research. Methods of the research is descriptive with a qualitatif approach.  Data collection is done through observation and recording of scores from each research stage. The results of the research show an increase in English business communication skills which can be seen from the average scores.